Potential role of adipose tissue and its hormones in burns and critically III patients. Issue 2 (March 2020) - Al-Tarrah, Khaled; Jones, Simon W.; Moiemen, Naiem; Lord, Janet M.
Highlights: The Obesity Paradox has been reported in critically ill populations. Burn injury and critical illness affect adipose tissue morphologically and functionally. Adipokines exert anti- and pro-inflammatory effects influencing patient outcomes. Abstract: Obesity has become a world-wide pandemic and is considered a major risk factor for various diseases. Despite this, recent intriguing clinical observations have been made suggesting that being overweight has some advantages. Overweight and some obese patients were reported to have significantly lower all-cause mortality, described as the 'obesity paradox'. This phenomenon resulted in increased research aimed at investigating the influence of adipose tissue on outcomes of various clinical states including critical illness. In this review, we summarise research findings on the effect burn injury and trauma-related critical illness have on adipose tissue and discuss potential mechanisms by which adipose tissue influences outcomes in burn and other critically ill patients. Burn injury and critical illness influence adipose tissue functionally and morphologically, with circulating levels of fat derived hormones, adipokines, altered in patients following injury and/or critical illness. As adipokines regulate a variety of processes including inflammation and metabolism, this disruption in the adipokine axis may explain the obesity paradox phenomenon observed in critically ill patients. We conclude that further research on the influence of individual adipokines on prognosis in burn and critically ill patients and the mechanisms involved is required to increase understanding of their therapeutic potential.